KEMAMPUAN PERTUMBUHAN EKONOMI MEMODERASI PENGARUH KINERJA KEUANGAN TERHADAP TINGKAT KEMISKINAN - Anindya Permatasari, Ni Ketut; Dwirandra, A.A.N.B (E-Jurnal Akuntansi, 2016)
The financial performance of allegedly non-linear effect on the level of poverty due to contingent factors, one of which is economic growth. This study aims to determine the effect of financial performance on poverty levels and the ability of financial performance moderating economic growth on poverty levels. Research by the scope of the 8 counties and one city in the province of Bali in 2009-2013 using quantitative and qualitative data with secondary data sources from Bali Provincial Finance Bureau and the Central Bureau of Statistics. Data has been tested and meets the classic assumption test and conformance test models with adjusted R2 = 43.2%, further research hypothesis testing using multiple linear regression analysis techniques and techniques Moderated Regression Analysis. The test results showed that the financial performance areas such as self-sufficiency ratio of the negative impact on poverty levels, the ratio of efficiency, effectiveness ratio and the ratio of revenue growth had no effect on levels of poverty, negatively affects economic growth on poverty levels. Economic growth was not able to moderate the financial performance on poverty levels.
Keywords: financial performance; economic growth; poverty